Entangled in the sierra. Plants uses as a sustainable strategy of survival among the Guarijio/Makurawe people of Sonora, Mexico - Bañuelos Flores, Noemi (2020)
The Guarijío/Makurawe people of Sonora are one of the most ignored native groups in Mexico´s Northwest region. From an ethnobotanical perspective, this paper analyzes the importance of plant resources for this indigenous community, according to their different uses. Some methodological technics included in depth personal interviews, direct-participative observation as well as community workshops.  Among key actors interviewed included the eldest people, housewives, rural workers, artisans, healers, cultural promotor, and the local governor.  Results show that the Guarijio exemplify a case of subsistence based on the uses of their biocultural heritage. Indigenous knowledges on vegetal resources represent the roots for any proposal of sustainable development focused on the improvement of wellbeing of this people.